PEMANFAATAN MINERAL ASBUTON SEBAGAI BAHAN STABILISASI TANAH - Neni Kusnianti (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
Asbuton is natural asphalt from Buton Island with great deposits and can beutilized, as a road material because it contains not only bitumen but also mineral with high lime content (CaCO3). The development of pure asbuton product, as a result of separation between bitumen and its mineral, so that mineral asbuton will be an environmental problem, if it is not utilized properly. Therefore, research is required to utilized the asbuton mineral as an alternative material for soil stabilization. The purpose of this research is to evaluate soil characteristics by laboratory test after stabilized with mineral asbuton and to find out the right proportion of mineral asbuton to improve soil support. In this research,soil characteristics stabilized mineral asbuton is compare with unstabilized soil to find out soil characteristics changes. The characteristics tested are Atterberg limit, gradation, density based on standard proctor density, CBR and unconfined compressive strength (UCS). Key words : asbuton mineral, soil stabilisati on, soil characteristics, CBR, UCS